The rise of lifelong learning and fall of adult education in India (UCL Press, 2019)
This article focuses on the dynamic relationships between the growing importance of lifelong learning (LLL) and consequent devaluation of adult education in national level educational policies, plans and programmes in India. It argues that by adapting the new paradigm of LLL, which is largely driven by marketcentric neoliberal principles, Indian adult education has lost its core and traditional learning ecology as there is a gradual submission to the pursuit of global economic competitiveness. It identifies three main reasons for the submission: (1) the metamorphosis from welfare to market principles in reforming education; (2) blind acceptance and misunderstanding of LLL as an educational and not a political discourse; (3) fragmented reforms in revamping adult education in India in the last decades.